Compensatory growth of Nile tilapia fingerlings subjected to food restriction and re-feeding at low temperatures (Revista de Ciências Agroveterinárias, 2022)
This study aims to investigate the effect of different periods of fasting and re-feeding on compensatory responses in Nile tilapia fingerlings and the frequency of muscle fiber distribution. A total of 108 Nile tilapia fingerlings with initial weight of 1.64 ± 0.41 g and mean initial length of 3.60 ± 0.39 cm were used for 55 days. The fish were distributed in a water recirculation system in a completely randomized design with three treatments and four replications: Control - CO - (fish fed until apparent satiation throughout the experimental period); fasting 10 - J10 - (fish fed to apparent satiation for 15 days, followed by 10 days of fasting and re-feeding to satiation for 30 days); and fasting 15 - J15 - (fish fed to apparent satiation for 15 days, followed by 15 days of fasting and re-feeding to satiation for 25 days). Fish from the J15 treatment showed unsatisfactory results in terms of productive performance (p
Keywords: muscle fiber growth; water temperature; fasting; tilapia; hypertrophy